Clinical Improvement of Dyspepsia Symptoms Following Eradication Treatment for Helicobacter pylori - Khaira Utia Yusrie; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2006)
The prevalence of Helicobacter pylori in patients with peptic ulcer in Indonesia is very high. It ranges between 90-100%. In general, patients with gastritis and peptic ulcer usually have dyspepsia symptoms. The pathophysiology of dyspepsia symptoms caused by Helicobacter pylori has not been clearly understood. However, it is assumed that the symptoms are correlated to various factors including inflammation, apoptosis damage, and increased secretion of gastric acid, atrophy and non-atrophy gastritis as well as the development of peptic ulcer. The main objective of treatment for Helicobacter pylori infection is elimination of Helicobacter pylori bacteria. Triple therapy has 80% success rate with no significant adverse events and minimal effect in inducing resistance to antibiotics. The success rate of eradication treatment in patients with peptic ulcer is 90%; while an evaluation on improvement of duodenal ulcus following eradication treatment with one month proton pump inhibitor treatment reveals 90% success rate. Keywords: Helicobacter pylori, improvement, dispepsia